PERILAKU KEJAHATAN DI KECAMATAN MALALAYANG KOTA MANADO - Pangaila, Farrid F. F. (HOLISTIK, Journal Of Social and Culture, 2014)
Man in her everyday will not be separated from the culture, because the human being is the creator and the user of culture itself. Human life because of the culture, while the culture will continue to live and thrive while people want to preserve the culture and not ruin it. Modern society as technologically complex products technology advances, mechanization, industrialization and urbanization gave rise to many social problems. As the impact of people and developing patterns of tingkah-laku stray from general norms, with the road do all alone for the sake of profit and personal gain, then disruptive and detrimental to the other party. Inconsistency, contradiction between ambitions and personal abilities, then such events is encouraging people to perform acts of criminal. Or, if there is an aspiration aspirations with personal potentialities, it will happen "maladjustment" economical (inability to adapt economically), which encourages people to act maliciously or doing criminal acts. Crime in the city of Manado, the biggest ratings in Malalayang subdistrict. The factors that really big chance against crime is a newcomer (urban) and consumption of alcoholic beverages (alcoholic beverages). With the onset of the social mobility of violent crime is a product of the cultural changes of motion as well as social change. Keywords : criminal, culture, Â social change